Домик на юге: [рассказы] / Маша Трауб - Трауб Маша (Проза Маши Трауб, 2016)
Экземпляры: ЦБ (20200316) / Инвентарный номер: 51915 / Цена: 60.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Т 65 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44